(untitled) - Goodman, David (New York, 1987)
This book introdce the industrial approprition of the rural productions process. The industrial substitution of the rural product. New directions in apppriationism and substitutionism...
Keywords: Nông nghiệp,Agriculture; Khía cạnh kinh tế,Economic aspects